Colchicine, an anti-rheumatic agent, as a potential compound for the treatment of COVID-19 - Carlo Perricone (Termedia Publishing House, 2020)
The outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has swept the world in a pandemic. The disease (COVID-19) is characterized by acute respiratory distress, and there is an immediate need for any effective agent before the development of a vaccine. Coronavirus-19 disease (COVID-19) is an infectious disease caused by SARS-CoV-2, a -coronavirus which causes pneumonia, requires intensive care unit hospitalization in about 10% of cases and can lead to a fatal outcome [1].